2022
DOI: 10.3390/membranes12100913
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Colour Response of Smart Sago Starch-Based Packaging Films Incorporated with Brassica oleracea Anthocyanin

Abstract: To meet the need for food products to be safe and fresh, smart food packaging that can monitor and give information about the quality of packaged food has been developed. In this study, pH-sensitive films with sago starch and various anthocyanin concentrations of Brassica oleracea also known as red cabbage anthocyanin (RCA) at 8, 10, 12, and 14% (w/v) were manufactured using the solvent casting process. Investigation of the physicochemical, mechanical, thermal, and morphological characteristics of the films wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In this regard, food packaging containing an indicator film can detect changes in the quality or freshness of the product, and respond by providing a visual warning to consumers. Briefly summarized, food spoilage can be tracked by alterations in pH as a reaction to the growth and metabolism of microorganisms or the development of organic acids and/or volatile amines (e.g., lactic acid formation in milk or ammonia/amino-sugar formation in meat) [320]. Commonly used synthetic indicators, such as bromothymol blue, methyl red and xylenol dyes, are known to be toxic and cancerogenic to human health [321].…”
Section: Organic Molecules In Smart Packagingmentioning
confidence: 99%
“…In this regard, food packaging containing an indicator film can detect changes in the quality or freshness of the product, and respond by providing a visual warning to consumers. Briefly summarized, food spoilage can be tracked by alterations in pH as a reaction to the growth and metabolism of microorganisms or the development of organic acids and/or volatile amines (e.g., lactic acid formation in milk or ammonia/amino-sugar formation in meat) [320]. Commonly used synthetic indicators, such as bromothymol blue, methyl red and xylenol dyes, are known to be toxic and cancerogenic to human health [321].…”
Section: Organic Molecules In Smart Packagingmentioning
confidence: 99%
“…[19][20][21][22] Starch, Ch, bacterial cellulose and chitin whiskers have been used in previous studies as materials used in freshness indicators. 2,14,15,23,24 Ch is a polysaccharide with properties used in many research as film material. 9,23,25,26 Yan et al have previously reported research on Ch film and BPA to monitor fish freshness.…”
Section: Introductionmentioning
confidence: 99%
“…Natural biopolymer materials are widely used as the matrix in indicator film because of their biocompatibility, non‐toxic and biodegradable properties 19–22 . Starch, Ch, bacterial cellulose and chitin whiskers have been used in previous studies as materials used in freshness indicators 2,14,15,23,24 . Ch is a polysaccharide with properties used in many research as film material 9,23,25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Another important contribution was made by Amariei et al [11], who evaluated the possibility of replacing polyethylene-based packaging for foodstuffs with a biodegradable alternative prepared via a mixture of alginate and agar, to which either ascorbic acid or calcium chloride was added. Furthermore, Che Hamzah et al (2022) [12] extracted anthocyanins from Brassica oleracea and used them in the preparation of pH-sensitive sago starch films. According to their results, the films exhibited a noticeable color response at different pHs.…”
mentioning
confidence: 99%